Mediators and Moderators of Reinforced Self-Affirmation as a Method for Reducing the Memory Misinformation Effect - Szpitalak, Malwina; Polczyk, Romuald (Frontiers in Psychology, 2021)
The misinformation effect (ME) occurs when an eyewitness includes information in their account that is incongruent with the event they witnessed, and stems from being exposed to incorrect external sources. This is a serious threat to the quality of witness testimony and to the correctness of decisions reached by courts. However, few methods have been developed to reduce the vulnerability of witnesses to misinformation. This article presents such a method, namely reinforced self-affirmation (RSA), which by increasing witnesses’ memory confidence makes them less inclined to rely on external sources of information and more on their own memory. The effectiveness of this method was confirmed in three experiments. It was also found that memory confidence, but not general self-confidence, is a mediator of the impact of RSA on ME, and that contingent self-esteem and feedback acceptance but not sense of self-efficacy or general self-esteem are moderators of this impact. It is concluded that RSA may be a promising basis for constructing methods which can be used by forensic psychologists in real forensic settings. Key words: witness testimony; reinforced self-affirmation; feedback; memory; misinformation effect; reducing suggestibility